Tumor organoid-immune co-culture models: exploring a new perspective of tumor immunity - Jing Wang; Xiaoyue Tao; Jialong Zhu; Zhe Dai; Yuanyang Du; Yiyang Xie; Xiaoyuan Chu; Gongbo Fu; Zengjie Lei (Cell Death Discovery)
Abstract Recent advancements in technology have significantly expanded the scope of tumor research, progressing from the study of individual cells to more intricate tissue and organ-level analyses. Tumor organoids have emerged as a highly realistic platform for investigating tumor growth, development, and their interactions with the surrounding microenvironment. However, a notable limitation of these organoids is their lack of the diverse cellular composition typically observed in actual tumors, which hinders their ability to fully replicate the complexity of the tumor microenvironment. Immune cells play a pivotal role, and tumor immunology has become a major research hotspot. Research in tumor immunology aims to elucidate how the immune system recognizes and attacks tumor cells, as well as how tumor cells evade immune surveillance. In recent years, there has been growing interest in co-culturing immune cells with tumor organoids, an approach that has yielded valuable insights into the intricate interactions between tumors and the immune system. The aim of this paper is to review and discuss the progress achieved in co-culturing tumor organoids with immune cells. By doing so, we hope to offer a new perspective and enhance our understanding of the complexity and diversity inherent in the tumor microenvironment.